Eugenol loaded chitosan nanoemulsion for food protection and inhibition of Aflatoxin B1 synthesizing genes based on molecular docking. (1st March 2021) - Das, Somenath; Singh, Vipin Kumar; Dwivedy, Abhishek Kumar; Chaudhari, Anand Kumar; Deepika,; Dubey, Nawal Kishore
Graphical abstract: Highlights: Encompassment of eugenol into chitosan nanomatrix (Nm-eugenol) by ionic gelation. Nm-eugenol exhibited improved fungitoxic and aflatoxin B1 inhibitory efficacy. Applicability of Nm-eugenol as novel methylglyoxal (AFB1 inducer) suppressor. In silico homology modeling of Ver-1 gene for aflatoxin B1 inhibition. Nm-eugenol as green preservative for protection of nutritional ingredients in rice. Abstract: The present investigation entails the fabrication and characterization of nanometric emulsion of eugenol (Nm-eugenol) encompassed into chitosan for assessing bio-efficacy in terms of in vitro antifungal actions, antiaflatoxigenic potential, and in situ preservative efficacy against Aspergillus flavus infestation and aflatoxin B1 (AFB1 ) mediated loss of dietary minerals, lipid triglycerides and alterations in composition of important macronutrients in stored rice. Nm-eugenol characterized by SEM, XRD, and FTIR exhibited biphasic burst release of eugenol. Reduction in ergosterol and methylglyoxal (AFB1 -inducer) content after Nm-eugenol fumigation depicted biochemical mechanism of antifungal and antiaflatoxigenic activities. In silico 3D homology docking of eugenol with Ver-1 gene validated molecular mechanism of AFB1 inhibition. Further, significant protection of rice seeds from fungi, AFB1 contamination and preservation against loss of rice minerals, macronutrients and lipids during storage suggested deployment of chitosan as a biocompatible wall material for eugenol encapsulation and application as novel green preservative for food protection.